Multi-scale approach for the analysis of the stress fields at a contact edge in fretting fatigue conditions with a crack analogue approach - C. Montebello; S. Pommier; K. Demmou; J. Leroux; J. Mériaux (Fracture and Structural Integrity)
This paper describes a novel method to model the stress gradient effect in fretting-fatigue. The analysis of the mechanical fields in the proximity of the contact edges allows to extract nonlocal intensity factors that take into account the stress gradient evolution. For this purpose, the kinetic field around the contact ends is partitioned into a summation of multiple terms, each one expressed as the product between nonlocal intensity factors, Is, Ia, Ic, depending on the macroscopic loads applied to the mechanical assembly, and spatial reference fields, ds, da, dc, depending on the local geometry of the part. This description is obtained through nonintrusive post-processing of FE computation and is conceived in order to be easily implementable in the industrial context. By using as input the macroscopic load, the procedure consists in computing a set of nonlocal stress intensity factors, which are an index of the severity of the stress field in the proximity of the contact edges. This description has two main advantages. First, the nonlocal stress intensity factors are independent from the geometry used. Secondly, the procedure is easily applicable to industrial scale FE model.